Performance of two serodiagnostic tests for loiasis in a Non-Endemic area. - Federico Gobbi; Dora Buonfrate; Michel Boussinesq; Cedric B Chesnais; Sebastien D Pion; Ronaldo Silva; Lucia Moro; Paola Rodari; Francesca Tamarozzi; Marco Biamonte; Zeno Bisoffi (Public Library of Science (PLoS), 2020)
Loiasis, caused by the filarial nematode Loa loa, is endemic in Central and West Africa where about 10 million people are infected. There is a scarcity of convenient, commercial diagnostics for L. loa. Microscopy requires trained personnel and has low sensitivity, while the serodiagnosis is currently not standardized. Individual case management is also important in non-endemic countries to treat migrants, expatriates and tourists. We retrospectively compared the performance of a Loa Antibody Rapid Test (RDT) and a commercial ELISA pan-filarial test on 170 patients, 65 with loiasis [8 with eyeworm, 29 with positive microfilaremia, 28 with neither microfilaremia nor history of eyeworm but eosinophilia and history of Calabar swelling (probable loiasis)], 95 with other common parasitic infections and no previous exposure to L. loa (37 with M. perstans, 1 with Brugia sp., 18 with strongyloidiasis, 20 with schistosomiasis, 5 with hookworm, 4 with Ascaris lumbricoides infection, 10 with hyper-reactive malarial splenomegaly), and 10 uninfected controls. The sensitivity of the RDT and of the ELISA were 93.8% (61/65) and 90.8% (59/65), respectively. For the RDT, most of the cross-reactions were observed in patients with M. perstans: 7/37 (18.9%), followed by 1/10 (10%) with hyper-reactive malarial splenomegaly and 1/20 (5%) with schistosomiasis. None of the 27 subjects infected with intestinal nematodes was found positive at this test. The ELISA is meant to be a pan-filarial assay, and reacted extensively with cases of M. perstans (95%), as expected, and also in 11/18 (61.1%) patients with strongyloidiasis and in 3/5 (60%) with hookworm infection. The RDT and the ELISA are both highly sensitive for the diagnosis of loiasis. The main difference lies in the extent of cross-reactivity with other parasites. Considering that the RDT is specifically meant for Loa loa infection, and its high sensitivity, this test could be a useful tool for the diagnosis of occult loiasis.